The effect of innovation on performance of manufacturing firms: the role of network ties - SARPONG PAULINA (KNUST, 2024)
A thesis submitted to the department of marketing and corporate strategy, kunst school of business, Kwame Nkrumah university of science and technology, in partial fulfillment of the requirements for the award of the degree of master of business administration